Complications of hypertensive disorders in pregnant women: systematic review - Albán, Ángeles C.; Moreira, Erika N.; Escudero, Ana I.; Mendoza, Diógenes E.; Alcívar, Fernando P.; Tumbaco, Dostin G. (Revista Gregoriana de Ciencias de la Salud, 2024)
Hypertensive disorders in pregnant women are medical conditions characterized by the persistent increase in blood pressure during pregnancy. Disorders such as gestational hypertension, preeclampsia, and eclampsia are major causes of maternal and perinatal morbidity and mortality worldwide. The objective was to identify the complications of hypertension during pregnancy, mentioning the causes that predispose to the condition. An exploratory systematic review was conducted, using the Web of Science, Scielo, and Google Scholar as sources of information on publications from 2013 to 2023. It was identified that the most common complications were: intrauterine growth restriction, hemorrhages, infections, heart attacks, strokes, and increased maternal-fetal mortality. Disorders such as preeclampsia are the leading cause of maternal mortality and cause complications for both the mother and the fetus. Furthermore, early detection and medical follow-up are crucial to minimize risks for both the fetus and the mother.